National Eye Service (1929)
1929 1929 1920s 12 pages NATIONAL EYE SERVICE [4] ACTON 33A, The Broadway, W.3. BRIXTON 65, Acre Lane. CAMDEN TOWN 156, Camden Road, N.W.1. EALING 24, Uxbridge Road, W.5. EARLS COURT 123, Warwick Road, S.W.5. EAST FINCHLEY 18, High Road, N.2. EAST HAM 318, Barking Road, E.6. EDMONTON 306, Hertford Road, N. ELEPHANT & CASTLE Planet House, 5, St. George's Road, S.E.1. FINSBURY PARK 29, Portland Road, N.4. HOLLOWAY 561, Holloway Road, N.19. HAMMERSMITH 227, Hammersmith Road, W.6. KILBURN 330, High Road, N.W. PECKHAM 93, Queen's Road, S.E.15. TOOTING 31, Upper Tooting Road, S.W.17. WHITECHAPEL 47, Turner Street, E.1. WALTHAMSTOW 181, Hoe Street, E.17. WANDSWORTH 46, Herondale Avenue, S.W.18. WIMBLEDON 84, High Street, S.W.19. WOOD GREEN 30, Turnpike Lane, N.22. WOOLWICH 7, Thomas Street, S.E. BASINGSTOKE 25, London Street. BATH 9, Bladud Buildings. 35, Brock Street. BEDFORD 1, St. Peters Street. BIRMINGHAM 8, Newhall Street. BLACKBURN 29, Preston New Road. BOURNEMOUTH 115, Old Christchurch Road. 28, Poole Hill. BRADFORD 38, North Parade. BRIGHTON 49, East Street. BRISTOL 61, Park Street. CAMBRIDGE 3A, Trumpington Street. CANTERBURY 59, St. Georges Street. CARDIFF 13, St. Andrews Crescent. 2, Dumfries Place. CHATHAM 24, Railway Street. CHESTER 59, Bridge Street Row. CLACTON-ON-SEA c/o Messrs. G. Bedwell & Son. Pianoforte Depot. COLCHESTER 35, Crouch Street. COVENTRY 10, The Quadrant, Warwick Road. CROYDON 17, Katharine Street. DERBY 115, Friargate. DISS 13, Market Hill. 292/841.4/1/61